“Nutritional Assessment in young people between 12 and 16 years old of two different educational realities, his relationship with a sedentary lifestyle and eating habits.2010” - Balladares Mazzini, Manuel (Revista Universidad de Guayaquil, 2012)
The nutrition-related problems in young adolescents are the problems associated with lack of knowledge in the selection of foods that you can choose from nutrients to meet the needs not do so for lack of information and training of specialists responsible for sharing information to improve the quality of life of the community dominate this on the lack of economic resources. The most common problems are protein-calorie malnutrition or protein-energy deficiency and overweight-obesity. He conducted research on this topic to determine the nutritional status of young adolescents in two schools in the city of Guayaquil with economic, social wanting different show if the purchasing power significantly affects the nutritional status performed a comparative study with a universe consists of 1147 young people between 12-16 years old. It took into account variables such as sex, age, weight, height, also were surveyed about the level of knowledge you have about nutrition and caregivers of the students themselves. The work was based on anthropometric measurements and surveys. The results were statistically tabulated and discussed, and it is proposed to implement an educational model of preventive measures.